1995
DOI: 10.1111/j.1365-2958.1995.mmi_17061093.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of AGT1 encoding a general α‐glucoside transporter from Saccharomyces

Abstract: Molecular genetic analysis is used to characterize the AGT1 gene encoding an alpha-glucoside transporter. AGT1 is found in many Saccharomyces cerevisiae laboratory strains and maps to a naturally occurring, partially functional allele of the MAL1 locus. Agt1p is a highly hydrophobic, postulated integral membrane protein. It is 57% identical to Mal61p, the maltose permease encoded at MAL6, and is also a member of the 12 transmembrane domain superfamily of sugar transporters. Like Mal61p, Agt1p is a high-affinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
189
2
18

Year Published

1997
1997
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(229 citation statements)
references
References 40 publications
14
189
2
18
Order By: Relevance
“…Maltose transport by AGT1-encoded transporters is therefore expected to be competitively inhibited by maltotriose and trehalose. In contrast, MAL11-and MAL61-encoded transporters are highly specific for maltose 8 , and this is probably true for the other MALx1-encoded transporters (they have almost identical sequences). This suggests that the dominant maltose transporter of the ale strain is that encoded by AGT1, since trehalose causes essentially complete (well over 85%) inhibition of maltose transport by this yeast.…”
Section: (-7'977-32mentioning
confidence: 83%
See 2 more Smart Citations
“…Maltose transport by AGT1-encoded transporters is therefore expected to be competitively inhibited by maltotriose and trehalose. In contrast, MAL11-and MAL61-encoded transporters are highly specific for maltose 8 , and this is probably true for the other MALx1-encoded transporters (they have almost identical sequences). This suggests that the dominant maltose transporter of the ale strain is that encoded by AGT1, since trehalose causes essentially complete (well over 85%) inhibition of maltose transport by this yeast.…”
Section: (-7'977-32mentioning
confidence: 83%
“…In addition, maltose and maltotriose compete for the same transporter in strains containing the AGT1-coded transporter, which carries several ␣-glucosides 8,24 , whereas glucose and maltose inhibit each other's transport in some strains, although they are not carried by the same transporters 3,23 . Jespersen et al 11 screened 5 ale yeasts and 25 lager yeasts and found that all contained MALx1 genes and all but one also contained AGT1 genes.…”
Section: -2863(9'8-32mentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of the MAL11 (AGT1) gene, whose product is important for maltotriose uptake 22 , was able to be specifically detected by the probe used, and in turn, its pattern of expression monitored. Comparison of patterns of sugar utilisation and expression of sequences detectable by the MAL31 or AGT1 probes highlighted significant strain differences.…”
Section: (-7'977-32mentioning
confidence: 97%
“…The strong expression of AGT1, especially for strains NCYC 1681 and NCYC 1309, which were capable of constitutive maltose utilisation, suggests the involvement of this gene product in the phenotype. This role is in keeping with the function of Agt1p as a transporter of ␣-glucosides, maltose and maltotriose included 22,49,54,55 . Further work will be required to determine whether attribution of this constitutive behaviour to the AGT1 gene product alone is correct.…”
Section: (-7'977-32mentioning
confidence: 99%